Optimalisasi Peran Orang Tua dalam Mendukung Gizi Seimbang dan Perilaku Hidup Bersih Sehat pada Remaja untuk Mencegah Stunting di Patuk, Gunungkidul - Benny Karuniawati; Nur Cahya Rachmawati; Lulung Lanova Hersipa; Mizan Prihastuti; Lutfi Annarahayu (Samodra Ilmu: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2026)
Background: Stunting is a condition of stunted growth due to chronic malnutrition and repeated infections, impacting a child's physical and cognitive development. Prevention can begin in adolescence, particularly in young women who are prospective mothers. The role of parents in providing balanced nutrition and PHBS is crucial to reducing stunting rates. In Yogyakarta Special Region, the stunting prevalence is 18%, with Gunungkidul being the highest at 22.2%. Objective: To increase parental understanding and involvement in supporting healthy eating patterns and PHBS to prevent stunting in adolescents. Methods: This community service activity lasted four weeks with 35 parents of students from Patuk 1 Junior High School as participants. The program included socialization and education on balanced nutrition and PHBS, training in developing healthy menus, interactive discussions, and monitoring and evaluation of changes in family eating and hygiene patterns to prevent stunting. Results: This program increased parental understanding of balanced nutrition and PHBS, as evidenced by a 35% increase in understanding scores. Parents began adopting healthy eating patterns with more protein and vegetables. Adolescent awareness also increased, as evidenced by better personal hygiene practices and consumption of nutritious foods. Conclusion: Optimizing the role of parents in supporting balanced nutrition and PHBS has proven to be an effective step in preventing stunting in adolescents.